Performance and emission characteristics of biogas-bio diesel fuelled RCCI engine at various butanol-gasoline injection timings. Issue 1 (November 2021) - Bhuvanashankar, P; Bindu, S B; Feroskhan, Mohammed Musthafa; Nova Hamsadhwan, B; Krishna Ganesh, V; Amarnath, M; Gobinath, N
Abstract: Energy, a basic need of human life, has been playing significant role behind many technological developments. Most of the world's commercial energy requirements are fulfilled by using fossil fuels. Combustion of fossil fuels releases toxic gases which in further turns as a source of pollution for the environment, globally. The present research work focused on minimizing the emissions that emerges during combustion in an IC engine through Reactivity Controlled Compression Ignition (RCCI) mode. The performance and emission characteristics of a single-cylinder CI engine are analyzed with 3 different fuels; biodiesel, butanol-gasoline (1:4 ratio), and biogas. The operational loads taken for the present study falls in the range from 5 N-m to 20 N-m at the engine speed of 1800 RPM. The influence of biogas on the emission characteristics is exclusively carried out with two different flow rates; 12lpm and 16lpm. The injection timings for butanol-gasoline blend are varied from 0 to 8ms. Fuel properties such as Viscosity, Vapor pressure, Density, Cloud point, Pour point, and Flashpoint are estimated. Engine parameters such as Brake Thermal Efficiency (BTE), Volumetric Efficiency (VE), HC, CO, NOx and smoke emissions, Peak pressure, Heat Release Rate (HRR), Ignition Delay, are analyzed. It is observed from the experiments that increasing injection time of pilot fuel - increases the HC and CO emissions; reduces the NOx emissions; decreases the smoke level with increase in biogas flow rate; and decreases the BTE, VE, and HRR